Gatekeeper versus auctioneer: A non-tatonnement result - Emmanuel S. de Dios; Grace T. Ong (University of the Philippines, School of Economics (UPSE), 2010)
A non-tatonnement process is described using the simplest demandand-supply model, involving the following: uniformly distributed agents; random matching of buyers and sellers; and a universal permission to engage in mutually acceptable trade at nonequilibrium prices. A sufficient condition is then stated where expected welfare gains are paradoxically greater when the number of market agents is restricted, compared to when all traders are allowed to participate.
Keywords: 330